A profile of Gestational Trophoblastic Neoplasia in a tertiary hospital in Surabaya, Indonesia - Aisyah Shabrina; Brahmana Askandar Tjokroprawiro; Nila Kurniasari; Hanik Badriyah Hidayati (Universitas Airlangga, 2023)
HIGHLIGHTS This study aimed to identify the characteristics of Gestational Trophoblastic Neoplasia (GTN). GTN is chemosensitive, but without appropriate therapy and follow-up, GTN will develop into complications and fatalities. ABSTRACT Objective: Gestational Trophoblastic Neoplasia (GTN) is a pregnancy-related malignancy due to abnormal proliferation of trophoblastic tissue. This study aimed to identify the characteristics of patients with GTN to help diagnose cases of GTN earlier and provide better treatment. Materials and Methods: This was a descriptive retrospective study on medical records of patients with GTN in Dr. Soetomo General Academic Hospital Surabaya, Indonesia, during the period of January 2018 to December 2020 with a total sampling technique. There were 41 patients with GTN included as study subjects. Results: Forty-one cases of GTN met the inclusion criteria out of the fifty medical records collected. The majority of patients aged 21 – 30 years old (34%) and had parity status without data (42%). Regarding the clinical profile based on prognostic factors, the predominant patients (71%) also had no data about the time interval between the end of the last pregnancy and the first time diagnosed by GTN, Those with more than 100,000 mIU/ml of beta-hCG levels were 32%, and those without metastases were 41.5%. Most patients belonged to the low-risk group (49%) and received chemotherapy (71%) with the MTX LD regimen (69%). Conclusion: GTN occurred predominantly in reproductive women that belonged to the low-risk group. Furthermore, chemotherapy is one of the chosen therapy for those patients.